Bibliometric and visual analysis of research on the links between the gut microbiota and pain from 2002 to 2021 - Mao, Menghan; Zhou, Yanyu; Jiao, Yingfu; Yin, Suqing; Cheung, Chiwai; Yu, Weifeng; Gao, Po; Yang, Liqun (Frontiers in Medicine, 2022)
Background and Aims: The gut microbiota is involved in the regulation of pain, which is proved by plenty of evidence. Although a substantial quantity of researches on the link between gut microbiota and pain has emerged, no study has focused on bibliometric analysis of this topic. We aim to present a bibliometric review of publications over the past 20 years and predict research hot spots. Methods: Relevant publications between 2002 and 2021 were extracted from the Science Citation Index-Expanded (SCI-EXPANDED) of the Web of Science Core Collection database (WoSCC) on April 22, 2022. CiteSpace (version 5.8 R3c), VOSviewer, the Online Analysis Platform of Literature Metrology and the R package bibliometrix were used to analyze and visualize. Results: A total of 233 articles have been published between 2002 and 2021. The number of publication outputs increased rapidly since 2016. The collaboration network revealed that the USA, Baylor College of Medicine, Vassilia Theodorou were the most influential country, institute, and scholar, respectively. Alimentary pharmacology & therapeutics and Gut were the most co-cited journal and Neurogastroenterology and Motility was the most productive journal. Visceral sensitivity, fibromyalgia, gastro-intestinal, chronic pain, stress, gut microbiome, LGG, brain-gut axis, SLAB51 and sequencing were the top 10 clusters in co-occurrence cluster analysis. Keyword burst detection indicated that brain-gut axis and short-chain fatty acid were the current research hot spots. Conclusion: Research on the links between the gut microbiota and pain has increased rapidly since 2016. The current research focused on brain-gut axis and short-chain fatty acid. Accordingly, SCFAs-mediated mechanism of pain regulation will be a research direction of great importance on the links between the gut microbiota and pain. This study provided instructive assistance to direct future research efforts on the links between the gut microbiota and pain.